Forward engineering for strategic gearing: A conceptual framework (Note) - Sharma, Subhash (2000)
The author presents a conceptual framework of `forward engineering' for strategic gearing of organisations. His framework is rooted in rationality creativity paradigm for gearing organisations for competitive challenges. By `forward engineering', the author implies creative, proactive and responsive action in the context of continuously changing competitive environment. The conceptual framework presented here is based on some new analytical tools that managers and administrators would find useful in gearing up for global competition in the context of liberalisation and globalisation. He presents illustrations of analytical tools of forward-engineering from Indian Tea industry. - Reproduced
Keywords: Note; Management